Protective role of angiotensin II type 2 receptor signaling in a mouse model of pancreatic fibrosis - Ulmasov, Barbara (American Physiological Society, 2009)
The renin-angiotensin system contributes to pathological processes in a variety of organs. In the pancreas, blocking the angiotensin II (AII) type 1 receptor (AT1) attenuates pancreatic fibrogenesis in animal models of pancreatitis. Because the role of the AII type 2 receptor (AT2) in modulating pancreatic injury is unknown we investigated the role of AT2 in pancreatic injury and fibrosis. Pancreatic fibrosis was induced by repetitive cerulein administration in C57BL/6 wild-type (WT) or AT2-deficient (AT2−/−) mice and assessed by morphology and gene expression at 10 days. There was no difference between WT and AT2−/− mice in the degree of acute pancreatic injury as assessed by amylase release at 9 and 12 h and by histological examination of the pancreas at 12 h. In contrast, parenchymal atrophy and fibrosis were more pronounced in AT2−/− mice compared with WT mice at 10 days. Fibrosis was accompanied by activation of pancreatic stellate cells (PSC) evaluated by Western blot analysis for α-smooth muscle actin and by immunocytochemistry; PSC activation was further increased in AT2−/− mice compared with WT mice. The level of pancreatic transforming growth factor-β1 mRNA and protein after repetitive cerulein treatment was higher in AT2−/− mice than in WT mice. Our results demonstrate that, in contrast to AT1 receptor signaling, AT2 receptor signaling modulates protective antifibrogenic effects in a mouse model of cerulein-induced pancreatic fibrogenesis. We propose that the effects of AII on injury-induced pancreatic fibrosis may be determined by the balance between AT1 and AT2 receptor signaling.